Pengaruh Motivasi Dan Disiplin Terhadap Efektivitas Kerja Pegawai Pada Kantor Kecamatan Ciputat Kota Tangerang Selatan - Mulyati Mulyati; Nurlaila Suci Rahayu Rais; Hasanah Hasanah (UNIVERSITAS RAHARJA, 2017)
The key success of Indonesia national development was the achievement of the society welfare as a whole. To achieve the goals, the Government must create the effectiveness in its activity process through the construction of one of its employees. From the result, there are still employees who do not come on time, and do not complete the work targets which have been set out in the work program due to lack of effective employment.This research aims to examine the problem of employee work effectiveness that is influenced by motivation and discipline shown by the implementation of good work, work attitude, and skill level of employees in Ciputat Sub-district office, South Tangerang City. This type of research used is descriptive research with the sample number of 35 people were taken by random sampling. The type of data used consists of primary and secondary data, by library research data collection tool, observation, interview, and questionnaire. Data were analyzed usingboth of qualitative analysis method and quantitative analysis. For statistical analysis use the Statistical Program for Social Sciences (SPSS) Release 20.0. Based on thetable of One-Sample Kolmogorov-Smirnov Test can be explained that the variabledata of discipline (X1), motivation (X2), and performance (Y) can be said normal.The heteroskedasticity test can be concluded that there is no heteroscedasticity in the regression model. The multicollinearity test concluded that there is multicollinearity among independent variables in the regression model. Since all variables have tolerance values > 0.10 and VIF values < 10, and is therefore in accordance with the assumption. The results of this research can be concluded:There is a significant effect between motivation on employee work effectiveness of in the Office of Ciputat Sub-District TangerangCity. This is explained from the equal result Ŷ = 24,610 + 0,237 X1 and significant test of correlation coefficient obtained thitung> ttable (2,593> 2,036). (2) There is a significant influence between the discipline on the effectiveness of employees in Ciputat District Office Tangerang City. This is explained from the equal result Ŷ = 24,610 + 0,497 X2 and significant test of correlation coefficient obtained thitung> ttabel (6,596 > 2,036). (3) There is a significant influence between motivation and discipline together towards the effectiveness of employees in the District Office Ciputat Kota Tangerang. This is explained from the the equal result Ŷ = 24,610 + 0,237 X1 + 0,497 X2 and significant test of correlation coefficient obtained Fhitung > Ftabel (22,553> 3,30)